The effect of mathematical belief, self-regulated learning, and self-efficacy on secondary school students' mathematics learning achievement - Rizqullah, Naufal; Syamsuri; Mutaqin, Anwar (Komunitas Ilmuwan dan Profesional Muslim Indonesia (KIPMI), 2025)
This study aims to measure the effect of mathematical beliefs, self-regilated learning, self-efficacy on mathematics learning achievement in mathematics. This study was conducted in public and private junior high schools in Serang City. The research method used was a survey. The population of this study was all junior high school students in Serang City, Banten Province, Indonesia. The sample in this study was 394 students. The sample selection was carried out in stages, starting with the selection of schools based on their accreditation using quota sampling. Furthermore, classes were selected from each school accreditation using cluster sampling. The instruments used in this study were questionnaires on mathematical beliefs, self-regulated learning and self-efficacy, and a list of final semester exam scores for the 2023-2024 academic year. The data collected were then analyzed using a partial least square - structural equation model (PLS-SEM) approach. The results obtained in this study were a structural equation model that describes the effect of mathematical beliefs, self-regulated learning, self-efficacy on mathematics learning achievement. The goodness of fit test showed that the model was classified as appropriate. The model shows that the variables that relative large effect on mathematics learning achievement are self-efficacy and self-regulated learning.